2020
DOI: 10.3844/jmrsp.2020.156.190
|View full text |Cite
|
Sign up to set email alerts
|

Mechatronic Systems to the Braking Mechanisms

Abstract: With the evolution of technology, the construction and geometry of the piston, together with the materials from which it is made, as well as the related manufacturing technologies, have been continuously improved. Thus, modern engines have become less polluting, working at higher temperatures and pressures. Body aerodynamics have been improved, leading to lower resistance forces from the air. Also, the internal losses of the engines, generated by friction, as well as those at the level of the tire-road interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 268 publications
0
3
0
Order By: Relevance
“…This finding is supported by the findings of Suman et al (2022), who observed that properly maintained vehicles are less likely to experience mechanical failure or breakdown, thereby reducing the risk of accidents caused by sudden malfunctions. Petrescu (2020) explained that appropriate tire inflation, regular rotation and tread depth checks contribute to optimal traction, improved handling and shorter braking distances. The study also confirms a positive relationship between policy enforcement and road accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by the findings of Suman et al (2022), who observed that properly maintained vehicles are less likely to experience mechanical failure or breakdown, thereby reducing the risk of accidents caused by sudden malfunctions. Petrescu (2020) explained that appropriate tire inflation, regular rotation and tread depth checks contribute to optimal traction, improved handling and shorter braking distances. The study also confirms a positive relationship between policy enforcement and road accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Modern vehicles are equipped with various safety systems such as anti-lock braking system (ABS), electronic stability control (ESC), airbags and traction control. Regular maintenance ensures that these safety systems function correctly and can provide the intended protection in the event of a collision or emergency (Petrescu, 2020). Appropriate tire inflation, regular rotation and tread depth checks contribute to optimal traction, improved handling and shorter braking distance.…”
Section: Development Of Hypotheses and Research Modelmentioning
confidence: 99%
“…In a previous study, a comprehensive analysis was conducted on the evolution of various automotive components and their increasing integration of electronic technologies. This analysis concluded that electronic innovation will permeate every vehicle component [ 6 ], including brake pedals [ 38 ]. Consequently, a research and innovation (R&D) strategy has been pursued to remain state-of-the-art in BBW technology, ensuring alignment with the latest advancements in the field.…”
Section: Methodsmentioning
confidence: 99%